Storytelling for Cinematic Virtual Reality: Audience´s Needs And Expectations - Ana Rita Jesus Costa (2018)
Virtual reality is set to redefine the rules of narrative structure, character development and storytelling in filmmaking. Despite being one the most popular technologies used to create virtual environments, 360 videos challenge audience immersion by imposing a linear narrative structure. This study seeks to reflect on the storytelling and entertainment value of film in the new age of virtual reality through the experiences, needs, and expectations of its potential audiences. Furthermore, it aims for the development of speculative narrative scenarios and their respective screenwriting guidelines in an effort to understand what stories are expected from audiences and how they can be scripted.